ANALYSIS OF ISLAMIC ECONOMIC DEVELOPMENT BASED ON BOARDING SCHOOLS IN THE CITY OF BANJAR - Munandar, Eris (Al-Infaq: Jurnal Ekonomi Islam, 2023)
This research aims to analyze the development of Islamic economics in Islamic boarding schools in Banjar City. The research method used is qualitative with a descriptive analysis approach, and the sample consists of 45 Islamic boarding school institutions taken using the saturated sampling method. The study results indicate that Islamic economics development in Islamic boarding schools in Banjar City is generally good in several aspects. However, there are still three aspects that are not optimal, namely the lack of activities on Islamic economic/financial studies, the absence of Islamic economic/zakat/financing institutions, and not being involved in the socialization/promotion of Islamic economic and financial products in Banjar City. The indicators of the perception of Islamic boarding school leaders towards Islamic economics and their contribution to the development of Islamic economics are good, but the mentoring of society trapped in loan sharks still needs to be improved.